2018
DOI: 10.1088/1361-648x/aac3ff
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in solid benzene molecular crystal

Abstract: Light-element compounds hold great promise of high critical temperature superconductivity judging from the theoretical perspective. A hydrogen-rich material, benzene, is such a kind of candidate but also an organic compound. A series of first-principles calculations are performed on the electronic structures, dynamics properties, and electron-phonon interactions of solid benzene at high pressures. Benzene is found to be dynamically stable in the pressure range of 180-200 GPa and to exhibit superconductivity wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…These unknown peaks are possibly induced by graphite, C 60 , and other modes. , On the one hand, therefore, we infer that the two higher transition temperatures may be from other new superconducting modes such as CK x , KH x , and K–CH x compounds induced by the reconstruction. On the other hand, as in our previous studies, , some internal and external factors can be the cause of high superconducting transition temperature, such as electronic correlations and pressure. The strong electronic correlations in K-doped p -terphenyl were implied by Baskaran and Fabrizio et al In this kind of low-dimensional organic system, therefore, the high superconductivity may be related with the electronic correlational effects.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…These unknown peaks are possibly induced by graphite, C 60 , and other modes. , On the one hand, therefore, we infer that the two higher transition temperatures may be from other new superconducting modes such as CK x , KH x , and K–CH x compounds induced by the reconstruction. On the other hand, as in our previous studies, , some internal and external factors can be the cause of high superconducting transition temperature, such as electronic correlations and pressure. The strong electronic correlations in K-doped p -terphenyl were implied by Baskaran and Fabrizio et al In this kind of low-dimensional organic system, therefore, the high superconductivity may be related with the electronic correlational effects.…”
Section: Resultssupporting
confidence: 66%
“…However, previous theoretical studies showed that PAH superconductors usually exhibit the antiferromagnetic (AFM) ground state and exist the strong electronic correlation effects, indicating that the superconducting mechanism is complicated in aromatic hydrocarbons. Our theoretical predictions have argued that electronic correlations or pressure could enhance high T c in aromatic hydrocarbons. Hence, organic-based compounds are candidates of high temperature or room temperature superconductors because the interaction of electrons with much higher excitation energy than the phonon energy can result in a substantially higher T c in these low-dimensional materials. , Thus, the higher T c can be expected in this kind of aromatic hydrocarbons.…”
Section: Introductionmentioning
confidence: 80%
“…Candidate PAH molecules with small Δ and a similar stacking type to those for the reported superconductors are listed in Figure c. Among the final 10 candidates, phenanthrene (1), picene (2), and coronene (8) are the experimentally reported superconductors, and benzene (7) was theoretically predicted to be a superconductor under high pressure . Note that triphenylene (3) was confirmed to be a superconductor by doping sodium in this work.…”
Section: Results and Discussionmentioning
confidence: 77%
“…4 (b) and (c)) induced by pressure. The pressure-induced phonon soening is a common behavior of superconductors at high pressure, [35][36][37] and it plays a crucial role in enhancing the electron-phonon coupling. 1,38,39 Therefore, the l of phase-b increases with the pressure increasing, which counteracts the decrease of u log .…”
Section: Resultsmentioning
confidence: 99%